Evaluation of BCL-2 and BAX Gene Expression in Hyperglycemia-induced NIH Cells - Saleem, Maryam; Zaman, Sher; Imran, Muhammad; Shuja, MalikNawaz; Imran, Muhammad (Scientific Inquiry and Review, 2021)
The incidence of Diabetes Mellitus (DM) type I and type II is very high all over the world. Excessive glucose levels and failure of one’s body to produce or manage glucose, trigger diabetes. Glucose is known to be responsive to NIH3T3 cells as it alters the expression of a range of genes associated with inflammation and apoptosis. In this study, the toxic effect of glucose was evaluated on NIH3T3 fibroblasts. Cells (NIH3T3) were cultured in media (DMEM), supplemented with 10% FBS and 1% Penicillin-Streptomycin. MTT assay was performed to check the toxic effect of glucose. NIH3T3 cells were treated with high glucose (30mM) for 24 hours. Trizol was used to extract the RNA followed by PCR reactions for gene expression analysis. Glucose treatment for 24 hours, modulated the expression of BCL-2 and BAX genes. The expression of BCL-2 was reduced while a significant increase was noticed in the expression BAX gene. Our results illustrated that glucose has some toxic effects on NIH3T3 cells. Glucose induces apoptosis by upregulating BAX and down-regulating BCL-2 expressions. Copyright(c) The Authors